Load Estimation and Design of Electrical Installation for Hotel in East Jerusalem - N. Sultan, Aladdin; Abu Judah, Laith (جامعة بوليتكنك فلسطين - طاقة, 2022)
This project aims at design a complete and stable electrical installation for a 17 floors hotel in East Jerusalem, with capacity of for 324 room 4 stars hotel that contains multi different floors, garage, mezzanine, three floors of parking, restaurant, service floor, praying floor and roof floor. Where the total energy consumption for load demand hours is 11,858 KWh per day. Due to large consumed energy and variation in energy demand, 3 transformers are installed with total capacity of 1000, 1250 and 1600 KVA. Moreover, 500 KVA backup generator and 60 KVA UPS as a backup power source for critical loads and. In addition, a 400KVA capacitor bank for power factor correction is installed. So, a continuity of service, dependability, and reliability can be achieved. The total cost of carrying out the electrical works combining hardware installation, engineering design and implementation for this project is estimated to be $6,569,331. Where, the hotel annual demand is about 4,328,038 KWh per year; with cost of energy is $779,046.84 per year.
CD , no of pages 235, طاقة 7/2022
Keywords: Load Estimation; Design of Electrical Installation